Antioxidant And Wound Healing Properties Of Cashew And Sweet Potato Shoot Extracts In Rats - Javadi, Mehdi (2009)

(untitled)
Ipomoea batatas (sweet potato) and Anacardium occidentale (cashew) shoots are commonly consumed vegetables which may have health benefits. The present study aims to investigate the polyphenol content, antioxidant activity and wound healing properties of ethanolic extracts of Ipomoea batatas and Anacardium occidentale shoots. Total phenolic content of these herbs were assessed using Folin-Ciocalteau assay and the antioxidant activity was measured utilizing free radical scavenging properties against the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH). Identification of flavonoids was done utilizing high performance liquid chromatography (HPLC). The results showed that ethanolic extracts of A. occidantale shoots had higher amount of total polyphenol (304.7 mg/GAE/g) than that of I. batatas shoots (86.5 mg/GAE/g). However the free radical scavenging activity (DPPH) was higher (70.53%) in I. batatas shoots than that of A. occidantale shoots extract (32.26%). The phenolic content of these two herbs and the free radical scavenging activities showed no positive relationship. Among the seven standards used, the main flavonoid found in both I. batatas and A. occidentale shoots was quercetin. The wound healing activity of ethanolic extract of I. batatas (sweet potato) and A. occidentale (cashew) shoots were investigated using excision wound models on Sprague-Dawley rats. Animals were randomly divided into four groups of eight rats and treated orally with (i) sweet potato shoots extract (250 mg/kg/day), (ii) cashew shoots extract (250 mg/kg/day), (iii) the negative control treated with distilled water only and (iv) the positive control treated with Gelam honey (250 mg/kg/day). Healing was assessed by the rate of wound contraction, antioxidant activity and tissue granulation. On day 14, the sweet potato and cashew shoots extract exhibited 96.0% and 90.5% reduction in the wounds area, respectively. The negative control group (distilled water) exhibited 86.8% and positive control group (honey) exhibited 96.7% wound reduction. The results also indicated that I. batatas and A. occidentale shoots extract possesses potent antioxidant activity by inhibiting blood lipid peroxidation significantly (P < 0.05) and caused increase in the superoxide dismutase (SOD), glutathione peroxidase and catalase activities. Histopathological examination of granulation tissues revealed increase collagen deposition in the treatments groups as compared to negative control group. The results suggest that I. batatas has antioxidant properties, which may be responsible and favorable for faster wound healing, and this plant extract may be useful to accelerate healing almost equivalent to honey.